(untitled) (The Journal of Geography Education in Africa, 2021)
This article presents the findings of the initial phase of an ongoing exploratory study that responds to a national imperative, to create teacher-initiated professional learning communities (PLCs), to improve the professionalism and capabilities of South African teachers. The overarching goal of the study is to understand how an emergent PLC in the form of an online Google Group for South African geography educators may enhance geography education and teacher professional development. The contributions made to the Southern African Geography Teachers Network Google Group over a six-month period were analysed and categorized according to themes and topics in the Grade 10, 11 and 12 Curriculum and Assessment Policy Statement (CAPS) curriculum. The findings, in shedding as they do, light on the curriculum sections receiving the most and least contributions, raise more questions than they provide answers. Areas requiring further research are identified. Our main contention is that the emergent PLC enabled through the Google Group offers exciting possibilities for teacher professional learning. As a bottom-up, online, easily accessible initiative, unrestricted by time or place constraints and with a growing membership, it may play an important role in enhancing the quality of teaching and learning in South African school geography.